2004
DOI: 10.1080/00207540310001652897
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process plans using a constraint-based tabu search approach

Abstract: A computer-aided process planning system should ideally generate and optimize process plans to ensure the application of good manufacturing practices and maintain the consistency of the desired functional specifications of a part during its production processes. Crucial processes, such as selecting machining resources, determining set-up plans and sequencing operations of a part should be considered simultaneously to achieve global optimal solutions. In this paper, these processes are integrated and modelled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 24 publications
(43 reference statements)
3
69
0
Order By: Relevance
“…However, T 6 is unavailable for operation 6, whose candidate cutting tools are T 7 and T 8 . The features, operations, and manufacturing resources information could be found in Table 5 of this paper, Table 4 of Li et al (2002a), Table 11 of Li et al (2004) and Table 5 of Huang et al (2012). Actually, the reported best result under condition 1 is 2535 according to the benchmarks.…”
Section: Computational Results Under Different Conditions and Criteriamentioning
confidence: 82%
See 1 more Smart Citation
“…However, T 6 is unavailable for operation 6, whose candidate cutting tools are T 7 and T 8 . The features, operations, and manufacturing resources information could be found in Table 5 of this paper, Table 4 of Li et al (2002a), Table 11 of Li et al (2004) and Table 5 of Huang et al (2012). Actually, the reported best result under condition 1 is 2535 according to the benchmarks.…”
Section: Computational Results Under Different Conditions and Criteriamentioning
confidence: 82%
“…Under condition 1, the best result of benchmarks [2527 by hybrid GA and SA in Li et al (2002a), 2527 by TS algorithm, 2535 by SA and 2667 by standard GA in Li et al (2004), 2527 by hybrid GA in Huang et al (2012), 2540 by Liu et al (2013)] is 2527. The best benchmark result was generated when operation 6 used cutting tool T 6 .…”
Section: Computational Results Under Different Conditions and Criteriamentioning
confidence: 92%
“…It should be pointed out that some assumptions [29,30] that are commonly used in most of the previous research works regarding scheduling were still taken for this study. The assumptions include:…”
Section: Case Studies and Discussionmentioning
confidence: 99%
“…The various output parameters and optimal solutions obtained by S 1 100 100 100 100 2 11 -0 100 1 100 100 100 3 11 100 -100 1 100 1 1 4 100 100 100 -100 100 100 100 5 11 1 100 100 -0 100 100 6 11 1 100 100 100 -100 100 7 11 100 100 100 100 100 -100 8 11 1 100 100 100 100 1 -Bhaskara Reddy [6] generated sequences in the initial population which violates the precedence relations even though the final reported optimal solution is a feasible one for the same case study. As the total number of 10, even a search technique is not essential to find the optimal solution.…”
Section: Output Parameters For Case Studymentioning
confidence: 99%
“…Li et al [11] researched the utilization of compelled based tabu scan approach for streamlining of process plans. Advance it was examined by Krishna and Rao [12] utilizing Ant colony algorithm (ACA) and found that the computational time has significantly decreased.…”
Section: Introductionmentioning
confidence: 99%